Bioremediation of urban river wastewater using Chlorella vulgaris microalgae to generate biomass with potential for biodiesel production (Research, Society and Development, 2020)
The production of biofuels through microalgae biomass represents a new generation of raw materials from renewable sources to meet society’s clamors and growing insertion in the market of fuels from products that could grant the planet a sustainable future. The present study assesses the biomass obtained from microalgae Chlorella vulgaris when grown in urban wastewater, extracting the lipids from the biomass and performing Gas Chromatography analysis of fatty acid methyl esters (FAME) composition after submitting the lipids through the transesterification process. The microalgae cultivation was monitored through chlorophyll (a) analysis and the highest cell growth was 845.8 µg L-1 using urban wastewater as growth medium. The nutrients of interest were monitored for primary concentration of 8.06 ± 0.06 mg L-1 of ammoniacal nitrogen, 12.27 ± 0.27 mg L-1 of nitrate and 21.22 ± 0.85 mg L-1 of phosphate, reducing about 99% of ammoniacal nitrogen and nitrate, along with reducing 87% of phosphate. The lipid constitution extracted from 3.7 g of dry biomass of Chlorella vulgaris after cultivation using urban wastewater, was 7.7%. The lipids extracted from the Chlorella vulgaris biomass are suitable biodiesel production regarding the amounts of FAMEs identified, after the analysis carried out, the comparison of the results obtained with other studies and the hypotheses evaluation.